The Problems of Supervision of Teacher Education for Islamic Religious Education Subjects in the State Junior High School (SMP) of the West Region of Sijunjung - Tugiah; Asmendri (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
Teaching is an obligation and routine carried out by every teacher by making it a responsibility in educating the nation's children. Teaching will be a problem if the fulfillment of the equipment is not fulfilled optimally, and when supervision is held it becomes a scourge and a frightening thing for subject teachers, one of which is Islamic religious education. The lack of completeness of equipment and limitations in knowledge of the use of teaching media are the reasons for the unpreparedness of teachers to be supervised